Anti-inflammatory effects of Crataeva nurvala Buch. Ham. are mediated via inactivation of ERK but not NF-κB. (13th March 2015) - Cho, Young-Chang; Ju, Anna; Kim, Ba Reum; Cho, Sayeon
Abstract: Ethnopharmacological relevance: Crataeva nurvala Buch. Ham. is an important medicinal plant in India, and its extracts and components were used to treat various inflammatory diseases, such as urinary tract infection, rheumatoid arthritis, and colitis. However, no systemic studies about anti-inflammatory effects of Crataeva nurvala Buch. Ham. and its underlying mechanisms of action have been reported. This study aimed to explore the anti-inflammatory effects of ethanol extracts of Crataeva nurvala Buch. Ham. (ECN). Materials and methods: The non-cytotoxic and maximal effective concentration of ECN was determined by measuring the formation of formazan from water-soluble tetrazolium salt in living cells. The inhibitory effect of ECN on nitric oxide (NO) synthesis was measured using Griess reagent, and Enzyme-linked immunosorbent assay (ELISA) was used to measure secreted tumor necrosis factor (TNF)-α and interleukin (IL)-6 protein levels. Furthermore, reverse transcription polymerase chain reaction (RT-PCR) and Western blotting analysis were used to assess the mRNA and protein expression of each inflammatory mediator or relating signaling protein, respectively. Results: A non-cytotoxic concentration of ECN (≤200 μg/ml) significantly reduced the production of NO and IL-6, but not TNF-α, in lipopolysaccharides (LPS)-stimulated RAW 264.7 macrophages. Decreased production of NO by ECN was correlated with reduced expression of iNOS at the mRNA and protein levels. However, cyclooxygenase (COX)-2 expressions at mRNA and protein level were not regulated by ECN. The mRNA expression of IL-6 and IL-1β, but not TNF-α, was also inhibited by ECN treatment in LPS-stimulated RAW 264.7 macrophages. Reduced production of inflammatory mediators by ECN was followed by decreased activity of mitogen-activated protein kinases (MAPKs), especially extracellular signal-regulated kinase (ERK), but not nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB). Conclusions: These results indicate that ECN inhibits LPS-induced inflammatory responses via negative regulation of ERK in murine macrophages, suggesting that ECN is a candidate for alleviating severe inflammation. Graphical abstract: